Enhanced gas sensing properties of flower-like ZnO nanostructure to acetylene. (March 2015) - Chen, W. G.; Gao, T. Y.; Li, Q. Z.; Gan, H. I.
<x content-type="archive" xml:space="preserve">Abstract</x> Well dispersed flower-like and rod-like zinc oxide (ZnO) microstructures were successfully synthesised by hydrothermal method with the assistance of hexadecyl trimethyl ammonium bromide. Microstructures and surface morphologies for both samples were characterised by X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy and high resolution transmission electron microscopy. Gas sensors were fabricated by screenprinting the as prepared ZnO nanostructures onto planar ceramic substrates. Then, their gas sensing properties were systematically investigated towards acetylene gas (C2H2). The products exhibit a high, reversible and fast response to C2H2 gas, and the flower-like ZnO architecture exhibits a better activity.